2017
DOI: 10.5812/jjm.14477
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Genes Encoding Toxin, Adhesion, and Antibacterial Resistance Among Various SCCmec Types of Methicillin-Resistant Staphylococcus aureus Isolated From Intensive Care Unit, Tehran, Iran

Abstract: Background: Most methicillin-resistant Staphylococcus aureus (MRSA) infections occur in health care settings; therefore, it is important to know about antimicrobial susceptibility, and carriage of virulence genes in S. aureus isolates. Objectives: The current study aimed at determining the prevalence of genes coding antimicrobial resistance, toxins, and adhesion factors among various SCCmec types of MRSA isolated from intensive care units (ICUs). Methods: From April 2016 to March 2017, a total of 200 MRSA spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Moreover, we have detected the pvl gene in 23.9% of MRSA and 9.8% of MSSA isolates. This was similar to the findings of Goudarzi and his colleagues, who reported the prevalence of pvl gene of 21.4% within MRSA isolates 37 , and Abiri and his colleagues who detected pvl gene among 21.5% of mecA positive MRSA strains 7 . We found that pvl gene was significantly prevalent in MRSA group (P=0.04).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, we have detected the pvl gene in 23.9% of MRSA and 9.8% of MSSA isolates. This was similar to the findings of Goudarzi and his colleagues, who reported the prevalence of pvl gene of 21.4% within MRSA isolates 37 , and Abiri and his colleagues who detected pvl gene among 21.5% of mecA positive MRSA strains 7 . We found that pvl gene was significantly prevalent in MRSA group (P=0.04).…”
Section: Discussionsupporting
confidence: 91%
“…They are known producers of different types of toxins and other virulence factors that shape up their clinical significance. Molecular studies have shown that some MRSA strains that carry tsst-1 and pvl genes 7 have the ability to produce toxins encoded by these genes responsible for severe infections such as TSS and necrotic pneumonia with a mortality rate up to 75% 19 . However, treating such infections is considered a challenge to physicians in view of their antimicrobial resistant properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different reports defined sea and seg genes as the most frequent enterotoxins genes associated with hospital-acquired sepsis [22]. Other report found tst and txt as the common enterotoxin genes in S. aureus isolates [23]. The distribution of enterotoxin genes differs according to geographic regions and types of studied patients.…”
Section: Discussionmentioning
confidence: 98%